THE EFFECTIVENESS OF THE COMBINATION OF DEMONSTRATION METHODS AND VIDEOS HOW TO CRUSH THE DENTALS OF GRADE IV STUDENTS OHI-S IN 2019 - Muliadi Muliadi; Asio Asio; Sukarsih Sukarsih (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2020)
Background: Teaching about dental and oral health has been given to elementary school students through the UKGS Puskesmas program, but the results of the initial survey conducted on 10 grade IV students only 3 students who have good OHIS criteria. Good oral hygiene can be achieved through good brushing and actually enhancing the skills in brushing your teeth through audio-visual (video) media and reproduction. This study aims to reduce the OHI-S status in Class IV Elementary School 23 / IX students in Pondok Meja Village, Mestong Jambi District in 2019, which can be seen through the results of the OHI-S examination. Methods: This quantitative study used a quasi-experimental non-randomized control group pretest and post-test design (non equivalent control group) with two groups, namely the intervention group and the control group. Total sampling used in sampling a number of 40 respondents. The analytical tool used the Wilcoxon test and the Mann-Whitney test. Results: The results of the study were determined by the criteria for pre-test dental and oral hygiene (OHI-S) for both grade IV students in the group with good criteria, especially (7.5%). The criteria for post-test dental and oral hygiene (OHI-S) of grade IV students who have good criteria are the intervention group (42.5% and the control group (7.5%) and the results of the unpaired group difference test show the number 0.001. Because the value of 0.001 <0.05 means that There is a difference between the OHI-S scores of the intervention group and the control group. Conclusion: combination of demonstration and video methods was significantly inprove the OHI-S